Law, Solidarity and the Limits of Social Europe Constitutional Tensions for EU Integration - Hartzén, Ann-Christine (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a [CC BY-NC-ND 4.0] License. It is free to read, download and share on Elgaronline.com. This thought-provoking book examines the socio-legal mechanisms that drive EU constitutional tensions, as well as the role of principles and values in re-directing EU law and policy towards a democratic Social Europe. It addresses the current limits of Social Europe in relation to different areas of EU law, offering a critical assessment of the present status of EU integration.